Valuation of Cocoa Agroforestry Ecosystem Services: Impacts on Biodiversity and Farmer Income - Sinambela, Jose (Jurnal Teknologi dan Ilmu Pertanian, 2025)
Cocoa agroforestry provides important ecosystem services such as biodiversity conservation, carbon storage, and support for pollination and nutrient cycling, which are often not market-valued. This study evaluates the economic value of non-market ecosystem services from local cocoa-agroforestry systems and their correlation with biodiversity and farmer income. Through a cocoa farmer survey and a contingent valuation approach, estimates of farmers' willingness to pay for the integration of shade trees in cocoa fields were obtained as a proxy for the value of ecosystem services. Results indicate that farmers value environmental services (e.g., pollinator habitat, soil fertility) at approximately IDR 2.5 million/ha/year. At the landscape level, cocoa agroforestry supports higher species richness than monoculture, with a loss of ~60% of forest species if shade trees are removed. Trade-offs appear moderate: low-shade intensification increases short-term production by ~40% but decreases carbon stocks and forest species. This study confirms that cocoa agroforestry can maintain biodiversity nearly equivalent to young secondary forests, while diversifying farmer incomes (fruit/timber). The economic valuation of ecosystem services justifies incentives (e.g., payment for ecosystem services) for farmers to maintain tree shade for the benefit of all.